Vitamin D deficiency in women with polycystic ovarian syndrome- a cross-sectional observational study in Indian subcontinent - Tomar, Neha; Raj, Aman Deep; Nayak, Suvendu Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Polycystic Ovarian Syndrome (PCOS) affects up to 18% of reproductive-age women, presenting with menstrual dysfunction, hirsutism, and metabolic complications. Vitamin D deficiency (VDD) shares features such as insulin resistance and obesity. Although global studies link hypovitaminosis D to metabolic risk, evidence in Indian women remains limited and inconsistent. This study assessed the prevalence of VDD and its association with metabolic and endocrine parameters in Indian women with PCOS. Methods: A cross-sectional study was conducted at Army Hospital Research and Referral, New Delhi, over 18 months (February 2022-February 2024). A total of 170 women (18-40 years) diagnosed with PCOS by Rotterdam criteria were enrolled. Participants were stratified by serum 25-hydroxyvitamin D (25(OH)D) levels: Group I (<30ng/ml) and Group II (≥30 ng/ml). Evaluations included anthropometry (BMI, waist circumference), hormonal profiles (LH, FSH, AMH, TSH), and metabolic markers (fasting glucose, insulin, HOMA-IR, HbA1c, cholesterol). Results: Most participants (89.4%, n=152) had suboptimal Vitamin D levels, while only 10.6% (n=18) were sufficient. Comparative analysis showed no significant differences (p>0.05) between groups in age, menstrual irregularities, Ferriman-Gallwey scores, ovarian morphology, or biochemical markers (LH, FSH, AMH, insulin, HOMA-IR, BMI). Spearman correlation confirmed no significant linear association between 25(OH)D levels and metabolic or hormonal variables. Conclusions: Hypovitaminosis D is highly prevalent among Indian women with PCOS. However, Vitamin D status did not significantly influence metabolic or endocrine dysfunction in this cohort, suggesting it may represent a comorbid condition rather than a causal factor. Larger longitudinal studies are warranted to clarify causal pathways and therapeutic relevance.